Avaliação e tratamento fisioterapêutico em trabalhadores portadores da síndrome do impacto do ombro - Camargo, Paula Rezende (2007)
This study evaluated the effectiveness of a standardized supervised therapeutic program performed during working hours on physical function and pain in workers with shoulder impingement stages I and II. Methods: Fourteen assembly line male workers (31.93 ± 5.86 years) with unilateral shoulder impingement stages I and II. The Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire evaluated function of the upper limbs. The McGill Pain Questionnaire quantified the pain by the number of words chosen and the pain rating index (PRI). Physical performance was evaluated by torque, total work and acceleration time that were measured bilaterally during isokinetic concentric abduction and lateral and medial rotations in the scapular plane, at 60°/s and 180°/s. Subjects completed an eight-week intervention program, consisting of cryotherapy, strengthening and stretching exercises, performed twice a week during working hours, and they were evaluated pre- and post-intervention. Results: DASH scores improved (P < 0.05) and the number of words chosen and PRI decreased (P < 0.05) at post-intervention. Torque improved (P < 0.05) in the abduction at 60°/s and in the medial rotation for both speeds after the therapeutic intervention. Total work increased (P < 0.05) at post-intervention for abduction and medial rotation at 60°/s and 180°/s. Acceleration time decreased (P < 0.05) in the abduction at 180°/s compared to the pre-intervention period. No changes were observed (P > 0.05) in any variable during lateral rotation. Conclusion: A rehabilitation program performed during working hours seems to improve symptom and physical performance in workers with shoulder impingement stages I and II.